PENERAPAN MEDIA AJAR MINIATURE OF INDONESIAN CULTURAL DIVERSITY UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA DI SMP NEGERI 22 SURABAYA - Muhammad Hafifulloh Ghoni; Muhammad Rizqi Khoirullah; Muslihah; Musyhidatul Chusna; Nabila Auliya Maulidah; RR. Nanik Setyowati; Masnidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to increase student participation and learning outcomes in the field of social studies by applying the Miniature of Indonesian Cultural Diversity (MOICD) teaching media in class 8H SMP Negeri 22 Surabaya. This research is a type of classroom action research (CAR) that was conducted in two cycles with the stages of planning, action implementation, observation, and reflection. In this study, the data collected were sourced from student participation observation sheets, learning outcomes, and supporting documentation. The results showed that there was a positive development both from the aspect of participation (from 73.8 to 86.5) and the completeness of student learning outcomes (from 63.3% with an average score of 77.4 to 93.3% with an average score of 85.2) in cycles I and II, respectively. This proves that the use of MOICD teaching media is effective in increasing students' active involvement and understanding of the material "Diversity of Indonesian Society", as well as in creating a more enjoyable, contextualized, and meaningful learning atmosphere.